Is The Size of The Fund Important in a Pandemic? Research for Polish Equity and Bond Funds - Dorota ŻEBROWSKA-SUCHODOLSKA (Communications of International Proceedings, 2021)
The research was aimed at checking the relationship between the size of the fund and its performance. The research was carried out on the basis of a linear and quadratic regression model, also taking into account lagging variables. The added value of the work is the research carried out in the initial phase of the pandemic for the Polish market using non-classical indicators based on VaR. The research also took into account the division into groups according to the size of the fund, for which the points of division were quartiles. One-way ANOVA was used to test the differences between the results of large and small funds. The results show a linear relationship between the size and performance of equity funds. Bond funds, in turn, are characterized by greater heterogeneity of results within the studied groups.
Keywords: fund size; value at risk; performance indicators; investment funds